Development and Evaluation of a Teacher Training Program in Artificial Intelligence Technology - Haoyang Huang (Journal of Advanced Research in Education, 2025)
This study aims to develop and evaluate a training program for teachers in artificial intelligence (AI) technology to enhance their ability to effectively utilize these technologies in teaching. Through a literature review, key content and methods for the training were identified, and corresponding evaluation indicators were designed. The study employed a mixed-methods approach, combining quantitative and qualitative data, to comprehensively assess the implementation effects of the training program. The results showed that the training significantly improved teachers’ understanding and application of AI technology, enhanced their teaching confidence, and had a positive impact on teaching practice. The study also explored factors affecting the training outcomes and proposed improvement suggestions, providing valuable references for future teacher training.